Evaluation of enterovirus 71 immune status in São Paulo state, Brazil - Adriana Luchs; Audrey Cilli; Denise H. Russo; Fernanda F. Costa; Rita de Cássia C. Carmona; Maria do Carmo S.T. Timenetsky (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
Antibodies to Enterovirus 71 (EV71) were evaluated in São Paulo State during 1999-2005. The titer of neutralizing antibodies against EV71 was determined by microneutralization assay, and a titer of > 1:8 was defined as indicative of protected immunity. Neutralizing antibodies to EV71 were observed in 12.4% (55/442) of sera samples, a low protective rate, suggesting that EV71 infection is uncommon in this region, but that there is a relatively high susceptibility to EV71 related diseases, which is worrying considering the recent Asian outbreaks. Also, a significant location-specific difference in seropositivity was observed. Neutralizing antibodies to EV71 were observed in 8.7% (21/241) of São Paulo metropolitan area sera samples, and 16.9% (34/201) of the sera samples from other municipalities. A high number of Brazilian residents live in country and coastal areas without adequate access to piped water or sanitation. This situation may contribute to the EV71 dissemination in these zones. The analysis of environmental samples could possibly make a valuable contribution to studies on the epidemiology of EV71.